Co-Creating Knowledge with Afro-Diasporic Communities : Reflections on a Participatory Research Process - Gruber, Valerie; Rothfuß, Eberhard (2021)
Whereas ethnographic and interview-based approaches tend to monopolize the power of definition in the hands of the scientist, Participatory Action Research (PAR) aims at reconfiguring knowledge production towards a collective, mutually beneficial process. To overcome objectifying hierarchies between the researcher and the researched is particularly significant in ‘traumatic places’ such as Salvador (Brazil) and Cartagena (Colombia), two major ports of arrival during the trade in enslaved Africans. In this presentation, we share insights into the PAR process developed with Afro-diasporic communities from both cities before and throughout the pandemic. We reflect on the potentialities and limitations of the transdisciplinary co-production of knowledge(s), in which research ethics, topics, methods, concepts and outcomes are co-created by relating academia, arts and community work. Finally, we discuss to what extent a ‘detachment process’ from the investigated social field is possible in participatory research, on the one hand, to abstract and theorize from the situated lifeworld, and on the other hand, to mirror the interpretations of the involved actors in the academic theorizations.